(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Bio preservatives are compounds derived from natural sources that can be used to extend food storage life and enhance food safety without any adverse health effects. Since food with synthetic preservatives is being avoided by consumers due to their long-term and short-term health effects, the demand for bio preservatives is largely increasing. Bio preservatives are considered an excellent alternative to chemical preservatives as they are generally recognized as safe (GRAS) and they can be used to retain the quality of food without causing any adverse health effects. This review explores the different agents which are employed as bio preservatives in the food industry, their mode of action, and their overall characteristics as a food preservative.